2004
DOI: 10.1248/bpb.27.180
|View full text |Cite
|
Sign up to set email alerts
|

Growth-inhibitory Effects of the Red Alga Gelidium amansii on Cultured Cells

Abstract: The objective of this study was to investigate the effects of Gelidium amansii, an edible red agar cultivated off the northeast coast of Taiwan, on the growth of two lines of cancer cells, murine hepatoma (Hepa-1) and human leukemia (HL-60) cells, as well as a normal cell line, murine embryo fibroblast cells (NIH-3T3). The potential role of G. amansii on the induction of apoptosis was also examined. The results indicated that all extracts from G. amansii, including phosphate-buffered saline (PBS) and methanol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 25 publications
0
19
0
3
Order By: Relevance
“…Yue-Hwa et al showed the anti-proliferative effect of G. amansii on hepatoma and fibroblast cells (22); however, there is no data on bioactive compounds isolated from G. amansii. A couple of compounds from other seaweeds have been studied, including polysaccharides and polyphenols.…”
Section: Resultsmentioning
confidence: 99%
“…Yue-Hwa et al showed the anti-proliferative effect of G. amansii on hepatoma and fibroblast cells (22); however, there is no data on bioactive compounds isolated from G. amansii. A couple of compounds from other seaweeds have been studied, including polysaccharides and polyphenols.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, agar is employed for cancer cell therapy because it can persuade the apoptosis of these cells in vitro (Chen et al, 2004). …”
Section: A Growing Worldwide Market For Cyanobacterial and Algal Metamentioning
confidence: 99%
“…G. amansii, both in phosphate-buffered saline (PBS) and methanol extracts from dried algae as well as the dimethyl sulfoxide (DMSO) extract from freeze-dried G. amansii agar, down regulated Hepa-1 and NIH-3T3 cell growth, but not the growth of HL-60 cells. Annexin V-positive cells were seen in methanol and DMSO extract-treated, but not PBS extract-treated Hepa-1 and NIH-3T3 cells, suggesting that the lipid-soluble extracts of G. amansii induced apoptosis [26].…”
Section: Gelidiummentioning
confidence: 92%